An Fe‐MIL100 Based Drug Delivery System for pH and Glutathione Dual‐Responsive Drug Release. Issue 44 (23rd November 2021) - Qi, Xiuyu; Li, Shanshan; Song, Xue‐Zhi; Gong, Yishu; Guo, Zhaoming; Cui, Changhao; Wang, Xiaofeng; Tan, Zhenquan
Abstract: Fe‐MIL100 with high Fe(II) content is synthesized at room temperature via a green synthesis process and used to form drug delivery system DOX@PEG‐MIL100 by loading doxorubicin (DOX) and coating with polyethyleneglycol (PEG). This drug delivery system shows pH and glutathione (GSH) dual‐responsive drug release behavior in response to tumor microenvironment and a high cytotoxicity in tumor cell line. Abstract : DOX@PEG‐MIL100 is synthesized by loading doxorubicin (DOX) on polyethyleneglycol (PEG) modified MIL100 by a green solution method. The large surface area and surface charge allow a high DOX loading rate. The adjustable Fe content provides glutathione (GSH) response behavior of MIL100. DOX@PEG‐MIL10 is applied as a pH and GSH dual‐responsive drug delivery system to improve the synergistic chemotherapy‐chemodynamic therapy.